Aliahj Dlicious Dessert Online Ordering Application - Sufri, Nur Liyana; Mohamed, Rozlini (Applied Information Technology And Computer Science, 2026)
Aliahj Dlicious Bakery is a local shop that offers a variety of desserts and food items, including pastries, cakes, and heavy meals. Currently, the shop manages customer orders manually using online platforms such as WhatsApp, Facebook, and Instagram, with orders recorded in notebooks and Excel sheets. This manual approach leads to several issues, including missed orders, slow processing, and limited engagement with customers. To overcome these challenges, the Aliahj Dlicious Dessert Online Ordering Application was developed. The goal of the application is to improve efficienc and enhance customer satisfaction. Developed using Flutter and Firebase, the application provides features such as online ordering, menu browsing, booking, delivery tracking, and feedback submission. Implementation of the application improves order accuracy, minimizes manual errors, and provides a seamless and user-friendly experience. Customers are now able to place orders anytime without visiting the shop physically. Future upgrades may include AI-based recommendations to personalize the user experience.